2021
DOI: 10.3390/medsci9020044
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines: Functions, Metabolism, and Role in Human Disease Management

Abstract: Putrescine, spermine, and spermidine are the important polyamines (PAs), found in all living organisms. PAs are formed by the decarboxylation of amino acids, and they facilitate cell growth and development via different cellular responses. PAs are the integrated part of the cellular and genetic metabolism and help in transcription, translation, signaling, and post-translational modifications. At the cellular level, PA concentration may influence the condition of various diseases in the body. For instance, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 188 publications
(245 reference statements)
6
80
0
Order By: Relevance
“…Some investigations point to an inverse relationship between colorectal cancer and polyamine intake, though this was not found in postmenopausal women with BMIs above 25 [25,26]. Several publications analyze the pros and cons of promoting PAs intake to increase longevity as well as prevention of new tumor formation in healthy subjects [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations point to an inverse relationship between colorectal cancer and polyamine intake, though this was not found in postmenopausal women with BMIs above 25 [25,26]. Several publications analyze the pros and cons of promoting PAs intake to increase longevity as well as prevention of new tumor formation in healthy subjects [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Horticultural crops are a good general source of vitamins, minerals and fibers among other compounds [28,29]. Many of these vegetables and fruits constitute substantial sources of PAs [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…While a PA catabolic pathway is dependent on the activity of three enzymes: N 1 -acetylpolyamine oxidase (PAOX), spermidine/spermine N 1 -acetyltransferase (SAT1), and spermine oxidase (SMOX) [7,[9][10][11]. Figure 2 The PA content in mammalian cells is tightly regulated [1][2][3] and it has been linked to important cellular roles. Polyamines are involved in the synthesis of proteins and nucleic acid and in the maintenance of their structure, in the regulation of the activity of ion channels, in cell proliferation, differentiation, and apoptosis, as well as in protection from oxidative damage [1][2][3].…”
Section: Polyamines Metabolismmentioning
confidence: 99%
“…The level of polyamines, including spermidine and spermine, were increased in patients with sepsis [12]. Two studies revealed serum [23] and polyamines, originally synthesizing from the arginine-ornithine pathway [24], to be involved in the RNA synthesis, transcription, and translation of human cells [25,26], as well as in several pathogens [24,27]. However, the interaction between host cells and the pathogen's polyamine requires elucidation.…”
Section: A Decrease In Cysteine and Lysinementioning
confidence: 99%